Khotbah yang Berwawasan Misiologis - Johana Ruadjanna Tangirerung (Institut Agama Kristen Negeri Toraja, 2021)
A church is then called a church if it carries out a mission. Preaching is part of the mission of the church. Preaching in the context of Christianity is a form of verbal preaching of the gospel. The Protestant Church places preaching at the center of worship. The strategic position of this sermon can be the starting point for a missiological sermon. Even though the sermon is the center of worship and one of the models of preaching the gospel, but whether these sermons have a missiological perspective. The purpose of this study is to describe the basis of the sermon which is called missiological insight. Another goal is that through this descriptive description, the church understands further the mission of the church in preaching the gospel and then becomes an evaluative starting point for present-day church sermons towards missionary-minded sermons towards missionary congregations. This study uses a descriptive qualitative approach, which relies on efforts to describe and describe the phenomenon of contemporary sermons to be confronted with the reality of the sermons offered, namely sermons with a missiological perspective. This research shows that preaching the gospel through preaching is a means of preaching the gospel and it is part of the church's mission and churches need to develop missiological-minded preaching for church growth. A sermon with a missiological perspective is a sermon that can direct and move all elements of the congregation to be involved in carrying out God's mission as a result of these sermons in the context of church growth.Gereja barulah disebut gereja jika melakukan misi. Berkhotbah adalah bagian dari misi gereja. Khotbah dalam konteks kekristenan adalah salah satu bentuk pemberitaan Injil secara verbal. Gereja Protestan menempatkan khotbah sebagai pusat ibadah. Posisi strategis khotbah inilah yang dapat menjadi titik berangkat khotbah yang misiologis. Sekalipun khotbah adalah pusat ibadah dan salah satu model pemberitaan Injil, akan tetapi apakah khotbah-khotbah tersebut sudah berwawasan misiologis. Tujuan penelitian ini adalah mendeskripsikan pendasaran khotbah yang disebut berwawasan misiologis. Tujuan lain adalah melalui uraian deskriptive ini gereja memahami lebih jauh misi gereja dalam pemberitaan Injil lalu menjadi titik berangkat evaluatif terhadap khotbah-khotbah gereja masa kini menuju khotbah yang berwawasan misiologis.Penelitian ini menggunakan metode pendekatan descriptive qualititavie, yang bertumpu pada upaya menguraikan dan mendeskripsikan fenomena khotbah-khotbah masa kini untuk diperhadapkan pada realitas khotbah yang ditawarkan yaitu khotbah yang berwawasan misiologis. Penelitian ini memperlihatkan bahwa pemberitaan Injil melalui khotbah adalah sarana pemberitaan Injil dan itu adalah bagian dari misi gereja dan gereja-gereja perlu untuk mengembangkan khotbah yang berwawasan misiologis untuk pertumbuhan gereja. Khotbah yang berwawasan misiologis adalah khotbah yang dapat mengarahkan dan menggerakkan seluruh elemen jemaat untuk terlibat dalam pelaksanaan misi Allah sebagai dampak dari khotbah-khotbah tersebut dalam rangka pertumbuhan gereja.